Small and Medium Enterprises (SMEs) with SWOT Analysis Method - Rakhmansyah, Mohamad; Wahyuningsih, Tri; Srenggini, Abdullah Dwi; Gunawan, I Ketut (Bright Institute, 2022)
This study aims to determine the strengths, weaknesses, opportunities and threats to SMEs in utilizing social media as a marketing tool and to find out the most effective marketing strategies to run in order to increase sales. The method used is SWOT analysis, and in data processing using excel. In collecting data using a questionnaire method distributed in the January 2021 period with a total of 226 respondents. The results obtained by SMEs in utilizing social media as marketing are in quadrant I, which means that the strategy used is a growth strategy, namely the SO strategy which is a strategy that uses strengths to take advantage of opportunities that exist in SMEs. Its implementation is to increase the intensity of promotions, maintain product and service quality, maintain and increase customer trust, be communicative to customers.